Enhanced CO2 hydrogenation to methanol over La oxide-modified Cu nanoparticles socketed on Cu phyllosilicate nanotubes. Issue 52 (October 2021) - Zuo, Jiachang; Chen, Kun; Zheng, Jianwei; Ye, Linmin; Yuan, Youzhu
Graphical abstract: Highlights: LaO x -modified CuSi-NT catalyst is prepared for CO2 hydrogenation to MeOH. LaO x -dopant stabilizes the surface Cu + /Cu 0 ratio of CuSi-NT. La/CuSi-NT benefits the formation of the HCOO* intermediate by CO2 hydrogenation. The catalyst can sustain 12% CO2 conversion and 80% MeOH selectivity for at least 200 h. Abstract: The use of Cu-based catalysts in CO2 hydrogenation to methanol (MeOH) has attracted considerable attention due to their low reaction temperature, low cost, and high activity. However, Cu nanoparticles are usually sintered under high-H2 atmosphere. The difficulty in keeping the Cu + /Cu 0 ratio stable during the reaction leads to the instability of Cu-based catalysts. In this work, La oxide-doped Cu nanoparticles socketed into parent Cu phyllosilicate nanotubes (La/CuSi-NT) are synthesized by exsolution in situ under a reducing atmosphere at elevated temperatures. They are used to catalyze CO2 hydrogenation to MeOH. Catalytic results show that the La/CuSi-NT catalyst is more stable than intact CuSi-NT and Cu-based catalysts prepared via traditional methods. Among the prepared catalysts, the 0.2La/CuSi-NT catalyst with the La/Cu molar ratio of 0.2 exhibits the highest MeOH yield of up to 428 mg gcat −1 h −1 and performance that remains stable for at least 200 h. Characteristic studies indicate that introducing a La promoter helps increase Cu + /Cu 0 ratios and confirm that LaO x species favor generating the formate species of CO2 hydrogenation. Therefore, MeOH synthesis through CO2 hydrogenation is intensified over the La/CuSi-NT catalyst.